Building resilience to conflict through food security policies and programs: An overview - Breisinger, Clemens; Ecker, Olivier; Maystadt, Jean-François; Trinh Tan, Jean-François; Al-Riffai, Perrihan; Bouzar, Khalida; Sma, Abdelkarim; Abdelgadir, Mohamed (International Food Policy Research Institute, 2014)
One and a half billion people still live in fragile, conflict affected areas. People in these countries are about twice as likely to be malnourished and to die during infancy as people in other developing countries.2 This outcome is often a direct consequence of conflict: conflict reduces food availability by destroying agricultural assets and infrastructure.